Sievers-Edgerton’s variants, Stang-Larsson’s rule, and Narten imperfects in Baltic long-vowel preterits - Yamazaki, Yoko (Baltistica, 2019)
There are two preterit-stem formations in Baltic: *ā-preterit and *ē-preterit. The *ē-preterit includes a category called “long-vowel preterit” that is characterized by the long root vowel. There are at least two hypotheses regarding their origin. First, it has been proposed that these long-vowel preterits may have originated from the imperfect form of Narten presents. Then, it has been suggested that long root vowels were introduced through Stang-Larsson’s rule operating on a variant of the Baltic preterit suffix *-ìyā-, where a vowel was lengthened and received a circumflex tone in a sequence *-V-ìyā- / *-̰-ìyā- > *--iyā (> *--ē). The second hypothesis explains the tone variation of the verbs in the root structure ◦ERK-, ◦EUK-, and ◦ĒK- (e.g., sprsti/sprsti, spréndžia/spreñdžia, spréndė/spreñdė ‘to stretch’
Keywords: Indo-European; Baltic; historical morphology; historical accentology; verb; long-vowel preterit; Sievers-Edgerton’s law; Stang-Larsson’s rule